THE INFLUENCE OF COUNTRY OF ORIGIN AND EWOM ON PURCHASE INTENTION WITH THE VARIABLE MEDIA BRAND IMAGE OF COMPUTER PRODUCTS IN JAKARTA - Andree Gunawan; Rodhiah Rodhiah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study was to test the Influence of Country of origin, and Electronic Word of Mouth (eWOM) on Purchase Intention with Product Brand Image Mediation Variable komputer